PENGARUH INTENSITAS KOMUNIKASI DAN KONSISTENSI GURU TERHADAP KARAKTER ISTIQOMAH BELAJAR SISWA DI MA DARUL LUGHAH WAL KAROMAH: ANALISIS REGRESI KUANTITATIF - Kuni Zakiyah M; Ainol Ainol; Umi Lailia Maghfiroh (Jurnal Manajemen Pendidikan, 2026)
This study aims to analyze the influence of teacher communication intensity and teacher behavioral consistency on students’ istiqomah learning character at MA Darul Lughah Wal Karomah through a quantitative regression approach. Istiqomah learning refers to students’ perseverance, discipline, and consistency in the learning process, which are essential values in Islamic boarding school education. This study employed a survey method using questionnaires distributed to fewer than 100 students selected through purposive sampling. The data were analyzed using multiple linear regression with the assistance of SPSS software. The findings revealed that teacher communication intensity had a positive and significant effect on students’ istiqomah learning character (β = 13.378; p < 0.05). Teacher behavioral consistency also showed a positive and significant influence (β = 0.034; p < 0.05). Simultaneously, both variables explained 48.1% of the variance in students’ istiqomah learning character (R² = 0.481). The novelty of this study lies in the integration of istiqomah as an Islamic value-based learning character construct into a quantitative regression framework within the context of pesantren education. These findings provide practical implications for strengthening character education through improving teacher communication and behavioral consistency